(untitled) (Fiep Bulletin - online, 2015)
The aging is product of life habits, behaviors and attitudes. Several pathologies osteo-muscle-rticulars begin in childhood and getting bad with while away. Physical Therapy have an important paper on older people respect a preventive and healing approach. The study aimed check the incidence of osteo-muscle-articulars dysfunctions and relate these pathologies existence with physical exercises practice. It was analyzed the out-patient’s handbook from a physical therapy clinic from Itajaí valley, SC, submitted for physical therapy treatment between January/2003 to July/2005. Considered data envolve gender, age, pathology, pain time and physical exercise practice. The sample was composed by 320 olders, 219 women and 111 men. These, 61,8% had chronic pathologies with diagnosis of osteoartrosis, especially in low back and knees. The pain time average was 7,9 years; this complaint was classified as continuous, but no very intense. The older people with concussed pathologies (17,9%) had lesions from falls, predominantly resulting in soft parts damages and superior members fractures. The acute pathologies, defined as first pain episode with inferior time of three months, was present in 13,6% of olders. Repetition of acute symptoms was observed in 6,7% of the patients, these relating intense pain. Physical activity was practiced just by 32,7% of elderlies, being more frequent in acute pathologies group and less frequent in group of concussed pathologies. Older people that looked for physical therapy attendance, in majority, had chronic osteo-muscle-articulars pathologies, with old pain complaints and mainly sedentary about physical exercises practice. Early physical therapy search and regular practice of physical exercises is recommended.